An Emerging Aerosol Climatology via Remote Sensing over Metro Manila, the Philippines - Lorenzo, Genevieve Rose (Archīum Ateneo, 2023)
Aerosol particles in Southeast Asia are challenging to characterize due to their complex life cycle within the diverse topography and weather of the region. An emerging aerosol climatology was established based on AErosol RObotic NETwork (AERONET) data (December 2009 to October 2018) for clear-sky days in Metro Manila, the Philippines. Aerosol optical depth (AOD) values were highest from August to October, partly from fine urban aerosol particles, including soot, coinciding with the burning season in insular Southeast Asia when smoke is often transported to Metro Manila during the southwest monsoon. Clustering of AERONET volume size distributions (VSDs) resulted in five aerosol particle sources based on the position and magnitude of their peaks in the VSD and the contributions of specific particle species to AOD per cluster based on MERRA-2. The clustering showed that the majority of aerosol particles above Metro Manila were from a clean marine source (58%), which could be related to AOD values there being relatively low compared to other cities in the region. The following are the other particle sources over Metro Manila: fine polluted sources (20%), mixed-dust sources (12%), urban and industrial sources (5%), and cloud processing sources (5%). Furthermore, MERRA-2 AOD data over Southeast Asia were analyzed using empirical orthogonal functions. Along with AOD fractional compositional contributions and wind regimes, four dominant aerosol particle air masses emerged: two sulfate air masses from East Asia, an organic carbon source from Indonesia, and a sulfate source from the Philippines. Knowing the local and regional aerosol particle air masses that impact Metro Manila is useful in identifying the sources while gaining insight into how aerosol particles are affected by long-range transport and their impact on regional weather.